Review of research into teachers’ beliefs at home and abroad - Luo, Lifei (International Journal of Humanities and Education Development (IJHED), 2023)
Teachers’ belief is an important research field in teacher education research, and related practices and research have been increasing in recent years. This paper summarizes and sorts out the research on foreign language teachers’ beliefs in primary and secondary schools at home and abroad from four aspects: the definition of the concept of teachers’ beliefs, the influencing factors of teachers’ beliefs, the research on the relationship between teachers’ beliefs and teaching practices, and the research on teachers’ beliefs and teachers’ professional development. Specifically, teachers’ beliefs are the views, attitudes, and psychological tendencies that teachers hold for truth about teaching-related factors in the teaching process. Its formation and change are mainly affected by personal background factors and social environment factors; Teachers’ beliefs and teaching behaviors influence each other, but they are not always consistent; Teacher professional development is the driving force behind changes in teachers’ beliefs. Finally, the paper points out that the future research on teachers’ beliefs in China can also expand the research objects, pay attention to the application of qualitative research methods, and focus on the dynamic research of teachers’ beliefs and the research related to teachers’ beliefs and teachers’ professional development.